THE ROLE OF NATIONAL ECONOMY IN THE FORMATION OF NATIONAL RESETTLEMENT SYSTEM - DOTSENKO, Anatoliy (Ekonomichna ta Sotsialna Geografiya, 2015)
The article describes the influence of the national economy, being one of the most important economic factors, on the formation of a national resettlement system on the example of Ukraine at the beginning of XXІ century, addressing the general and special features of the national economy, especially its development and structure. The author analyses basic theoretical issues related to the influence of national economy transformation on the development of the national resettlement system in Ukraine.

У статті розглянуто вплив одного із найважливіших економічних чинників – національної економіки – на формування національної системи розселення на прикладі України на початку XXІ ст. Розкрито загальні та особливі ознаки національної економіки, особливості її розвитку та структури. Розглянуті основні теоретичні питання впливу трансформації національної економіки на розвиток національної системи розселення населення України.
РОЛЬ НАЦІОНАЛЬНОЇ ЕКОНОМІКИ У ФОРМУВАННІ НАЦІОНАЛЬНОЇ СИСТЕМИ РОЗСЕЛЕННЯ
Keywords: system; resettlement; settlement; transformation; market; structure; система; розселення; поселення; трансформація; ринок; структура